1998
DOI: 10.1177/030098589803500402
|View full text |Cite
|
Sign up to set email alerts
|

Equine Malignant Lymphomas: Morphologic and Immunohistochemical Classification

Abstract: Gross lesions, microscopic appearance, and immunophenotyping are reported in a retrospective study of 31 cases of equine malignant lymphoma. Immunohistochemical studies were performed on archived formalin-fixed, paraffin-embedded tissues. Monoclonal antibodies to surface glycoprotein BLA.36 and intracytoplasmic domains of mb-1 and B29 were used to document the presence of B lymphocytes in the equine tumors. Polyclonal antibody to CD3 and monoclonal antibodies to T-lymphocyte markers CD3 and CD5 revealed the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
113
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 44 publications
1
113
1
4
Order By: Relevance
“…In equine lymphoma, an extensive immunohistochemical study has been reported, 31 utilizing antibodies and techniques suitable for examination of formalin-fixed, paraffinembedded tissues. 32 In the present study, immunohistochemical analysis performed on lymphoid tissues from horses 1 and 2 supported the results of the flow cytometric analysis of the leukemic cells.…”
Section: Jvim 15 209 Mp 145mentioning
confidence: 99%
“…In equine lymphoma, an extensive immunohistochemical study has been reported, 31 utilizing antibodies and techniques suitable for examination of formalin-fixed, paraffinembedded tissues. 32 In the present study, immunohistochemical analysis performed on lymphoid tissues from horses 1 and 2 supported the results of the flow cytometric analysis of the leukemic cells.…”
Section: Jvim 15 209 Mp 145mentioning
confidence: 99%
“…Cutaneous lymphoma in the horse often exhibits a T-cell rich B-cell or TCRBCL immunophenotype (Kelley and Mahaffey 1998, Seahan et al 1980, Dettileux et al 1989) that is considered to represent a relatively non-aggressive subtype of the disease (de Brujin et al 2007). However, many classi fication and prognostication issues that are mainly based on histopathology and immunohistochemistry remain unresolved or are still controversial awaiting their clarification (Scott and Miller 2003).…”
Section: Dettileaux Et Al 1989)mentioning
confidence: 99%
“…However, in the present case some of the small-sized cells were positive for B-cell markers (CD20, CD79α) or histiocytic markers (HAM56, MAC387). Such a variety of reactive cells has not been confirmed in TCRBCLs reported in humans and other mammalian species [2,3,6,17,20,21,23,26]. The difference between human and cynomolgus monkey may be due to different cytokine profiles produced by neoplastic B-cells.…”
mentioning
confidence: 95%
“…In humans, TCRBCL is characterized by an admixture of large-sized neoplastic B-cells and small-sized reactive T-cells and the latter comprises more than 50% of the whole cellular population [19]. This type of lymphoma has been reported not only in humans [3,[19][20][21], but also in other mammalian species including dog [2], cat [6,23], pig [26], and horse [17]. Histological features of TCRBCL in these animals are considered to be very similar to those of human TCRBCL.…”
mentioning
confidence: 99%